Theoretical issues in the conservation of contemporary art - Rosario Llamas-Pacheco (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The passage of time is inexorable and will have an inevitable repercussion on current works of art. In the case of contemporary art, many of the values included in artworks are linked to the pristine appearance and the conscious and specific use of a kind of matter. Transformation has an impact on the artistic intention, therefore, and since it is impossible to avoid the change, a deep reflection is necessary on the concept of premature ruin. Thanks to the artist it is possible to document the current production in relation to the mutation and inevitable transformation of matter, determining when the degradation will affect the quiddity of the works of art.